Bridging the Gap Between Research and Practice: Predicting What Will Work Locally. (June 2020) - Joyce, Kathryn E.; Cartwright, Nancy
This article addresses the gap between what works in research and what works in practice. Currently, research in evidence-based education policy and practice focuses on randomized controlled trials. These can support causal ascriptions ("It worked") but provide little basis for local effectiveness predictions ("It will work here"), which are what matter for practice. We argue that moving from ascription to prediction by way of causal generalization ("It works") is unrealistic and urge focusing research efforts directly on how to build local effectiveness predictions. We outline various kinds of information that can improve predictions and encourage using methods better equipped for acquiring that information. We compare our proposal with others advocating a better mix of methods, like implementation science, improvement science, and practice-based evidence.